Change Pattern and Driving Mechanism of Construction Land in China’s Undertaking Industrial Transfer Demonstration Area: Taking the Wanjiang City Belt along the Yangtze River as an Example - Cao, Yuhong; Liu, Meiyun; Cao, Yuandan; Chen, Chen; Zhang, Dapeng (Earth Sciences Research Journal, 2020)
The construction land includes the urban land, rural residential areas and other construction land. The Wanjiang City Belt along the Yangtze River is an important demonstration area for undertaking industrial transfer in China. With the accumulation of factors relative to economic development, the construction land has increased sharply, and the regional ecological security pattern is facing new challenges. After collecting the image interpretation data of multi-period land use of the Wanjiang City Belt, the work studied the characteristics of construction land change pattern since 1995 and its driving mechanism based on the GIS platform, land use transfer matrix, expansion intensity index, hotspot analysis and mathematical statistics. The results showed that: (1) From 1995 to 2015, the urban land and other construction land in the Wanjiang City Belt have increased, but the rural residential areas decreased in 2010-2015. The three types of land had the largest changes in 2005-2010 and the change in the other construction land was particularly prominent. (2) The hotspots for construction land expansion are mainly in urban areas with rapid economic development such as Hefei, Wuhu, Ma’anshan and Tongling, where the land use changes most severely. (3) The driving factors for the change of construction land area include natural and social factors. Among social and economic factors, the GDP, industrial added value, secondary output value and urbanization rate are the main driving forces for changes. In the past 20 years, the construction of China’s Undertaking Industrial Transfer Demonstration Area has changed the land optimal allocation and intensive use mode in the region, providing the basis for resource development and utilization, economic development and industrial structure adjustment.